Biological control of cyanobacteria using polyphosphate accumulating bacteria isolated from activated sludge - Dudhane, Amol; Mhaindarkar, Vaibhav P. (Journal of Pure and Applied Microbiology, 2011)
Increased input of nutrients into water body leads to massive proliferation of cyanobacteria and other algae. This ultimately results in the eutrophication of the water body. The cyanobacterial blooms exert negative environmental impacts such as extensive growth of alga, bad odor, decline in dissolved oxygen, production of cyanotoxin, decreased growth of submerged aquatic organisms and change in taste of water. This results into reduction in qualitative and quantitative properties of water. Various chemical based methods of eutrophication control are suggested by researchers but those endanger the aquatic ecosystem. Considering hazardous effect of chemical agents, biological agents may be used more safely. Here we have shown that polyphosphate accumulating bacteria (PABs) isolated from activated sludge are efficient in reducing cyanobacterial blooms up to 95.56% by trapping phosphorus in metapolyphosphate form. This is the first study that provides direct evidence that use of these microorganisms gives promising result in controlling cyanobacterial blooms and consequently eutrophication process without affecting the ecosystem of water body.
Keywords: Cyanobacterial blooms; Eutrophication; Metapolyphosphate accumulating bacteria